Factors associated with eyestrain complaints in corporate customer care center computer users - Vincent Gerfy; Arfail Devaryo; Missael Fillindo (International Journal on Health and Medical Sciences, 2022)
Eye tiredness, according to medical science, is a symptom induced by excessive efforts of the visual system, which is not in perfect condition, to attain visual clarity. Pain or throbbing around the eyes, blurred vision, double vision, difficulty focusing, sore eyes, red eyes, watery eyes, headaches, and dizziness accompanied by nausea are all symptoms of eyestrain. According to a study conducted by the Japanese Ministry of Health (2004), 91.6% of computer operators complained of eye fatigue. This study is quantitative and employs a cross-sectional research approach. According to the findings, the majority of computer users complain of eye fatigue. Furthermore, there is a relationship between age and lighting level with complaints of eye fatigue among computer users at PT. Telekomunikasi Indonesia, Tbk's Corporate Customer Care Center (C4) in 2009 with a Pvalue of 0.023 and the lighting level variable has an OR value of 30.00, indicating that the lighting level has a risk of 30 times the incidence of complaints of eye fatigue in computer user workers at C4 PT. Telekomunikasi Indonesia, Tbk. The variables refractive error, eye rest, and monitor distance have no correlation with complaints of eye tiredness. To alleviate worker complaints of eye fatigue, The company's advice is to offer lighting in accordance with the required standards for computer workplaces, namely 300 Lux, and to conduct periodic eye checks for employees. When working with a computer, workers should avoid wearing contact lenses because eye fatigue will be felt more rapidly. Meanwhile, future researchers are likely to use a reaction timer to objectively assess eye fatigue and a case-control study design to evaluate other characteristics connected to eye fatigue.